2002
DOI: 10.1172/jci15506
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of phosphodiesterase 4D in mice shortens α2-adrenoceptor–mediated anesthesia, a behavioral correlate of emesis

Abstract: IntroductionCyclic nucleotides cAMP and cGMP are degraded by at least 11 families of phosphodiesterases (PDEs 1-11) classified according to their gene sequence, substrate specificity, biochemical regulation, and sensitivity to inhibitors (1, 2). The cAMP-specific PDE4 has attracted considerable attention for the treatment of airway inflammatory diseases, since its inhibition results in attenuated inflammatory responses (1,3,4). However, the therapeutic potential of PDE4 inhibitors has been limited by the side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
140
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(142 citation statements)
references
References 34 publications
1
140
1
Order By: Relevance
“…If it were possible to identify the subtype (s) responsible for the beneficial and the side effects associated with PDE4 inhibition, then subtype-selective inhibitors devoid of the tendency to induce nausea and vomiting could be developed. The mechanism of the emetic response associated with PDE4 inhibitors is thought to be a consequence of the inhibition of PDE4D subtype [9,10], But which PDE4D subtype was involved in the nausea action was unclear. Recently advance suggested that PDE4D modify the stroke risk in the Swedish population [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If it were possible to identify the subtype (s) responsible for the beneficial and the side effects associated with PDE4 inhibition, then subtype-selective inhibitors devoid of the tendency to induce nausea and vomiting could be developed. The mechanism of the emetic response associated with PDE4 inhibitors is thought to be a consequence of the inhibition of PDE4D subtype [9,10], But which PDE4D subtype was involved in the nausea action was unclear. Recently advance suggested that PDE4D modify the stroke risk in the Swedish population [3].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were conducted following procedures previously described [9,10]. Briefly, mice were anesthetized with the combination of xylazine (10 mg/kg, sigma, USA) and ketamine (80 mg/kg, Zhejiang Xianju Pharmaceutical Co. LTD, China) administered in a single intraperitoneal injection.…”
Section: Assessing the Anesthetic Reversal Effect Of Pde4 Inhibitorsmentioning
confidence: 99%
“…Rolipram [(±)-4-(3-cyclopentyloxy-4-methoxyphenyl)-2-pyrrolidone], one of the most widely studied PDE inhibitors (Schneider 1984;Wachtel 1983a,b) inhibits all PDE4 subtypes (MacKenzie and Houslay 2000; Robichaud et al 2002). However, the recent availability of genetically modified mice that lack either the PDE4B or PDE4D genes has made studies exploring the role of the PDE4 subtypes possible (Jin et al 1999(Jin et al , 2005Jin and Conti 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Rolipram is well absorbed, shows good bioavailability, and after oral or subcutaneous administration in rat, the serum half-life of rolipram is about 1 h Kuhne 1988, 1993). Rolipram inhibits all PDE4 subtypes (MacKenzie and Houslay 2000; Robichaud et al 2002) and has no reported activity at other PDEs, enzymes, or neurotransmitter receptors. Unfortunately, one of the major limitations within the PDE4 field is the lack of commercially available subtype-selective inhibitors.…”
Section: Introductionmentioning
confidence: 99%